The Role of Group Work in Enhancing Undergraduate Students’ Writing Skills - Taye, Tamirat; Teshome, Gemechis; Negash, Alemayehu (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Writing is essential for academic and professional success. This mixed-methods study, combining surveys and semi-structured interviews, aims to investigate the role of group work in enhancing undergraduate students’ writing skills. It focused on 40 second-year students at a university in Ethiopia, selected through purposive sampling, and four EFL teachers. Researchers used structured questionnaires and semi-structured interviews to collect data from students and teachers. Statistical methods were employed for quantitative data, whereas content analysis was utilized for qualitative data. Results indicated that students encountered specific writing difficulties, particularly related to grammar and vocabulary. Nevertheless, collaborative work significantly improved their writing abilities by fostering teamwork, facilitating constructive criticism, and promoting engaged participation in the teaching and learning process. Students reported heightened motivation and involvement during collaborative tasks, substantially improving their writing skills. Based on the findings, recommendations include integrating collaborative learning techniques into the curriculum, dedicating more time to group-focused writing instruction, emphasizing the benefits of collaborative learning, implementing regular assessments to monitor progress, and encouraging diverse writing approaches beyond traditional classroom settings. Highlighting adaptable and student-focused teaching methods is crucial for enhancing overall writing skills among undergraduate learners.